Two-phase flow structures in a helically coiled microchannel: An experimental investigation - Sira Saisorn; Phakkhanan Benjawun; Adirek Suriyawong; Lazarus Godson Asirvatham; Pranab Kumar Mondal; Somchai Wongwises (Physics of Fluids, 2023)
At the microfluidic scale, the utilization of helically coiled channels (HCCs), also known as a spiral channel, for two-phase flow offers numerous advantages in various applications. Existing articles mainly focus on the macro-scale transport, examining secondary flows induced in curved channels. The increasing demand, however, for innovative miniature equipment for thermal energy management emphasizes the importance of comprehending gas–liquid micro-scale flow in curved channels. Unfortunately, despite a vast body of literature on this paradigm, there is still a lack of systematic investigations into the underlying facets of two-phase micro-scale transport in HCCs. To address this gap, our study conducted experiments on adiabatic two-phase air–water flow inside an up-flow helical micro-scale tube. The tube had a hydraulic diameter of 0.87 mm, a coil diameter of 50 mm, and a helical pitch of 20 mm. The primary aim was to explore the impact of centrifugal force on flow pattern, void fraction, and frictional pressure drop characteristics. Additionally, we carefully examined the phase separation phenomenon influenced by the secondary flows induced by the curved channel. In particular, we compared the gas-core flow pattern (either throat-annular flow or annular flow), void fraction, and frictional pressure drop obtained from our experiments on the helical tube with corresponding results based on straight micro-scale channel configurations for an Eötvös number of approximately 0.01. In summary, this study delves deep into the crucial aspects of two-phase micro-scale transport in HCCs, contributing to a better understanding of these systems for future advancements in micro-channel applications.
Keywords: Heat Transfer and Boiling Studies; Heat Transfer and Optimization; Fluid Dynamics and Thin Films